배양 조건에 따른 한우 수정란의 발달과 초자화 동결 후 수정란의 생존성 비교 - 조상래(농촌진흥청 축산기술연구소; 최선호(농촌진흥청 축산기술연구소; 최창용(농촌진흥청 축산기술연구소; 손준규(농촌진흥청 축산기술연구소; 이풍연; 고응규; 김현종(농촌진흥청 축산기술연구소; 연성흠; 손동수 (Journal of animal reproduction & biotechnology (Online), 2010)
We investigated the cleavage rate and blastocyst yield for each culture condition to enhance tolerance of cryopreservation of bovine IVF embryo with relatively lower cryo-tolerance compared to in vivo embryo. The cleavage rate and blastocysts yield for CR1aa, IVMD, IVD, CR1aa+10% FBS were 73.2, 69.3, 72.8, 68.5% and 44.1, 30.8, 33.3, 48.0%, respectively. The values did not differ among each treatments without serum. For embryo vitrification, In vivo and In vitro blastocysts were exposed to VS1 (10% glycerin, 0.1 M glucose, 0.1 M sucrose, PEG 1%) for 5 min, and VS2 (10% glycerin, 10% EG, 0.2 M glucose, 0.2 M sucrose, PEG 2%) for 5 min and then VS3 (10% glycerin, 30% EG, 0.3 M glucose, 0.3 M sucrose, PEG 3%) for 1 min. The exposed embryos were then loaded into the 0.25 ml plastic straws and then plunged into liquid nitrogen. The straws were held for period of 1 to 2 weeks before thawing. In embryo viability, no differences in blastocyst re-expansion rates were found between in vivo and in vitro embryos. whereas expansion-BL rates was significantly higher for in vivo-derived embryos (72.7%) when compared to in vitro-derived embryos (51.4%), respectively (P<0.05). In conclusion, our results indicate that combined use of CRIaa culture medium with vitrification might enhance tolerance of cryopreservation for bovine IVF embryo production. KCI Citation Count: 0